Littératie et droits en matière de santé et de services sociaux - Karine Collette; Jean Rousseau; Isabelle Clerc; Sylvie Clamageran (Communication)
Quebec’s Health and Welfare Commissioner mandated the authors to examine within a literacy framework the issues of awareness and information regarding the rights to health and social services. Using literature review, semi-directed interviews and telephone surveys, they describe the perception, knowledge and experience that past beneficiaries as well as health and social services workers/volunteers have of the rights and responsibilities of those that benefit from such services. Using a discourse analysis approach, they also studied the sociocognitive logics of the most socio-economically fragile interviewed participants, through their telling of their health experiences.